1985
DOI: 10.1007/bf01914288
|View full text |Cite
|
Sign up to set email alerts
|

Schottky contributions in chemical thermodynamics

Abstract: Cryogenic heat-capacity determinations provide a useful tool for the determination of the energetic spectrum of condensed phases and also reveal information on their discrete electronic level structures as well. We have been interested in applying these techniques to actinide elements and have in recent months been working up the techniques to unravel the corresponding data for the lanthanide compounds--where opposite trends in cationic masses and molar volumes provide an opportunity to test theories useful fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…If LaPO 4 (m) is ignored, the difference between calculated and measured heats of formation for the monazite phases fall on a systematic trend with a negative slope (increasing atomic number implies increasingly negative deviation from experiment; in other words, as atomic number increases, the calculated heats of formation become less and less exothermic relative to the measured heats of formation). There will also be Schottky-type contributions for some of the phases (Westrum, 1985), but these cannot be responsible for the overall 40 kJ/mol differential between the measured and calculated enthalpies, as they should be close to zero for compounds with no crystal field stabilization (Y, Sc, La, Gd).…”
Section: Formation Of Repo 4 From Re 2 O 3 and P 2 Omentioning
confidence: 99%
See 1 more Smart Citation
“…If LaPO 4 (m) is ignored, the difference between calculated and measured heats of formation for the monazite phases fall on a systematic trend with a negative slope (increasing atomic number implies increasingly negative deviation from experiment; in other words, as atomic number increases, the calculated heats of formation become less and less exothermic relative to the measured heats of formation). There will also be Schottky-type contributions for some of the phases (Westrum, 1985), but these cannot be responsible for the overall 40 kJ/mol differential between the measured and calculated enthalpies, as they should be close to zero for compounds with no crystal field stabilization (Y, Sc, La, Gd).…”
Section: Formation Of Repo 4 From Re 2 O 3 and P 2 Omentioning
confidence: 99%
“…There will also be Schottky-type contributions for some of the phases (Westrum, 1985), but these cannot be responsible for the overall 40 kJ/mol differential between the measured and calculated enthalpies, as they should be close to zero for compounds with no crystal field stabilization (Y, Sc, La, Gd).…”
Section: Thermal Corrections Tomentioning
confidence: 99%
“…The adjustment to stoichiometric end member composition was made by utilizing the heat capacities of vitreous silica [13] and of a-quartz [13] for the vitreous and crystalline materials, respectively. The Schottky-function-like [14] deviation between the heat capacity of the vitreous phase and that of the corresponding crystal for each disilicate (M 2 O AE 2SiO 2 ; M = Li, Na, K) is shown in figure 3. The heat capacity of vitreous and crystalline Li 2 O AE 2SiO 2 has been measured between T = 6 K and T = 304 K by Bennington et al [4] and the percent deviation of the measured sample with reference to our smoothed curve is shown in figure 4.…”
Section: Resultsmentioning
confidence: 99%
“…The relative differences in total C p value for the lithium disilicates at T = 6.5 K is 2.5 compared with 1.25 at T = 103 K; for sodium disilicates at T = 5.5 K is 2.25 compared with 1.1 at T = 101 K; for potassium disilicates at T = 6.6 K is 2.2 compared with 0.99 at T = 100 K. These values are consistent with observations for other vitreous-crystalline systems. Westrum has demonstrated that the difference in the C p vs. T curves of a vitreous phase and the corresponding crystalline phase is a Schottky function [14,16]. The difference curves, [C p (vit.)…”
Section: Discussionmentioning
confidence: 98%
“…To perform this simulation, temperature dependences of thermodynamic functions of the substances involved in the process are required, as well as the reliable values of enthalpy of formation. Since the heat capacity of lanthanide compounds (with the exception of diamagnetic lanthanum and lutetium) contains an anomalous contribution due to the interaction of the 4f‐electron shell with the crystal field (Schottky anomaly), 22 estimation of their heat capacity by the Neumann‐Kopp rule can have a significant error, especially if the structural types do not match. Due to this reason there is a need for experimental measurement of the heat capacity in a wide temperature range.…”
Section: Introductionmentioning
confidence: 99%